THE PROCEDURE OF FORMING ECONOMIC CONCEPTS IN HIGH SCHOOL STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
In the article, the structural components of scientific notions its basic conceptions of forming of economic notions at pupils of higher forms in the process of teaching are considered.